2004
DOI: 10.1002/bmc.318
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and bioaccumulation of fenitrothion in rat liver

Abstract: The biodegradation of fenitrothion O,O-dimethyl-O-(3-methyl-4-nitro phenyl) phosphorothioate was investigated in rat liver after administration of various doses (5 mg/100 g body weight and 20 mg/100 g body weight) in acute treatment and 1 mg/100 g body weight in chronic treatment. High performance liquid chromatography of the pesticide and its metabolites formed in liver in acute treatment showed time-dependent sequential conversion of pesticide into three major metabolites within 24 h. These metabolites were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…22,23,36 Cytochrome P450 was considered to be responsible for those metabolisms (phase I metabolism). 21,45 The two major degradation pathways of FNT by C. elegans in the current study were also found in other animals, such as rats, 46 female goats, 47 and birds. 48 Furthermore, aromatic hydroxylation during the metabolism of FNT in birds, 48 which has not reported in plants and soil, was also detected in C. elegans.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 78%
See 1 more Smart Citation
“…22,23,36 Cytochrome P450 was considered to be responsible for those metabolisms (phase I metabolism). 21,45 The two major degradation pathways of FNT by C. elegans in the current study were also found in other animals, such as rats, 46 female goats, 47 and birds. 48 Furthermore, aromatic hydroxylation during the metabolism of FNT in birds, 48 which has not reported in plants and soil, was also detected in C. elegans.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 78%
“…elegans can metabolize a wide variety of xenobiotics as those reported in human and animal studies through N-oxidation and N-deethylation, , demethylation, and hydroxylation. ,, Cytochrome P450 was considered to be responsible for those metabolisms (phase I metabolism). , The two major degradation pathways of FNT by C. elegans in the current study were also found in other animals, such as rats, female goats, and birds . Furthermore, aromatic hydroxylation during the metabolism of FNT in birds, which has not reported in plants and soil, was also detected in C.…”
Section: Resultssupporting
confidence: 48%
“…Cytochrome P-450 enzymes may be implicated in both the hydroxylation and reduction reactions of MNP; however a combination of peroxidase and oxidase activities may be responsible for the condensation reaction. Recently, the reduction product 4-amino-3-methylphenol was found to be a major metabolite of fenitrothion metabolism in rat liver in vivo; however condensation products were not reported (28).…”
Section: Resultsmentioning
confidence: 99%
“…The pattern of distribution and elimination of fenitrothion in male and female rats was similar regardless of receiving a single nontoxic dose (15 mg/kg) exposure, a single toxic dose (105 mg/kg) exposure, or repeated nontoxic dose exposure (15 mg/kg every other day five times, and then treated with 15 mg/kg fenitrothion) (392,401) (405).…”
Section: Experimental Studiesmentioning
confidence: 99%